Conditions of the Mora Peninsula between the years (1382-1460) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The Mora peninsula was one of the Byzantine regions occupied by the Crusaders in the fourth Crusade and the Byzantines regained their influence following the victory of Micheal VIII Palaiologos (1259-1282) over William II Villehardouin (1246-1278 AD) In the year 1259 AD, since the end of the fourth Crusade, the Mora peninsula had witnessed the establishment of a number of Latin Americans in the region. The Venetian ruled various parts of the Peloponnese. The Byzantines gave great importance to it and made it autonomous. However, their aspirations collided with the Ottoman ambitions and the Latins In particular the state of internal rebellion by the aristocratic landowners, which forced the inhabitants of the Mora peninsula to adapt to the situation of the power struggle surrounding it to control the area of ​​the Peloponnesis. Therefore, their policy varied and changed towards those forces, And the subsequent dependence and hostility and confrontation, which led to the weakness of the region and the lack of resources due to the proliferation of foreign wars and internal rebellions, in addition to other factors related to the nature of the Turkish invasion on the one hand and the turbulent conditions suffered by the Byzantine Empire on the other hand, T ultimately fell to the Ottomans.